Genetic Aspects of Dental Erosive Wear and Dental Caries - Amela Tulek; Aida Mulic; Maria Runningen; Jannike Lillemo; Tor Paaske Utheim; Qalbi Khan; Amer Sehic (Hindawi Limited, 2021)
Objectives. The present review aims to give an overview of the literature focusing on novel genetic aspects of dental erosion and dental caries. Once the tooth erupts into the oral cavity, the regenerative capability of enamel is fundamentally limited due to the loss of dental epithelium during eruption. The susceptibility or resistance to dental erosion and caries is presumably a result of environmental, phenotypic, and/or genetic influence. Even though it is evident that individuals frequently exposing their teeth to acid and sugar are at high risk of developing dental erosion and caries, the findings exclusively based on these factors are elusive. Data resources and study selection. The present review was based on data collected from the National Library of Medicine database with different combinations of the following terms: "tooth," "dental," "dentin," "enamel," "erosion," "erosive wear," "caries," "decay," "gene," and "genetic." A total of forty-six studies met the inclusion criteria. Data were extracted by one reviewer and verified by another. Conclusion. The high prevalence of erosion and caries among certain groups, and observations that not all individuals appearing to be at risk develop these lesions, has sparked research on identifying genetic effects to these conditions. A connection of genome-wide and candidate gene studies has increased considerably in the literature. This review reveals largely varying success among studies, demonstrating the difficulties of developing the study with adequate sample sizes and durable phenotype definitions that permit enough statistical power to identify genetic contributors.